Digital Transformation in Welfare Provision: The Case of Indonesia’s Jamsostek-Mobile Platform - Pramasanti, An Nisa; Saragih, Tarimantan S; Supriadi, Arief Dahyan; Setianingrum, Triyastuti; Jatmiko, Dipto; Minza, Wenty Marina; Harimurti, Suryo Wahyu Utomo; Handriani, Inge; Mahaganti, Fergie S; Pradana, Fadly Eka; Hutabara, Rendra H; Siregar, Denny; et al. (Journal of Posthumanism, 2025)
Digital transformation has profoundly reshaped the governance and delivery of welfare services worldwide. In Indonesia, this shift is exemplified by the Jamsostek Mobile (JMO) application developed by BPJS Ketenagakerjaan, a state-run platform integrating employment-related social protection services. This article analyzes JMO as a case study of digital transformation in welfare provision, highlighting how user experience (UX) emerges as a critical infrastructure in mediating access, trust, inclusion, and democratic legitimacy. Through mixed-methods research—surveys (n=486), usability tests, and qualitative interviews—the study unpacks the cognitive, emotional, and institutional dimensions of platform-based welfare delivery. We argue that UX in digital welfare systems should be reframed as a public good and infrastructural element, not a secondary technical feature. This reconceptualization is necessary to ensure equitable access, reduce digital stratification, and promote transparent, empathetic, and citizen-centered welfare governance in an increasingly platformized state.